2018
DOI: 10.26444/jpccr/92743
|View full text |Cite
|
Sign up to set email alerts
|

Betulin and betulinic acid in cancer research

Abstract: Introduction. Terpenes are the largest known class of organic compounds, widely distributed in plants. They are grouped considering the number of isoprene units in their structure; hence, the group consisting of 30 carbon atoms is called triterpenes. These compounds have a wide range of biological features. Objective. The aim of this review was to comprehensively discuss the role of betulin and betulinic acid as potent anticancer agents, including various studies determining their efficiency in cancer treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
(44 reference statements)
1
40
0
Order By: Relevance
“…Attention was also drawn to other activities of BA and BE, and researches have been carried out for over two decades to determine the entire spectrum of their growing biological applications. So far, several reviews combining the current knowledge about betulin or betulin acid have been published (Yogeeswari and Sriram 2005;Fulda 2008Fulda , 2009Ghaffari Moghaddam et al 2012;Gheorgheosu et al 2014;Csuk 2014;Król et al 2015;Rastogi et al 2015;Zhang et al 2016;Hordyjewska et al 2018). However, most of them focus on either BE Fig.…”
Section: Betulinic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention was also drawn to other activities of BA and BE, and researches have been carried out for over two decades to determine the entire spectrum of their growing biological applications. So far, several reviews combining the current knowledge about betulin or betulin acid have been published (Yogeeswari and Sriram 2005;Fulda 2008Fulda , 2009Ghaffari Moghaddam et al 2012;Gheorgheosu et al 2014;Csuk 2014;Król et al 2015;Rastogi et al 2015;Zhang et al 2016;Hordyjewska et al 2018). However, most of them focus on either BE Fig.…”
Section: Betulinic Acidmentioning
confidence: 99%
“…The ubiquity of triterpenoids in natural environment resulted in conducting various studies in order to explore and use their therapeutic potential. Although triterpenes were considered biologically inactive for a long time, numerous researches in recent years have revealed plenty of their properties, such as anti-cancer, anti-inflammatory, antioxidant, antiviral, hepatoprotective, or cytotoxic (Hordyjewska et al 2018). However, with several exceptions, pentacyclic triterpenes usually account for less than 0.1% of plant organs dry weight (Jäger et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The role of betulin derivatives as natural antioxidants obtained from birch bark extracts is not only the significant increase of the SOD levels and the MDA level decrease of EAC-bearing mice but also the decrease of cytostatics side effects. Moreover, the antitumor activity of betulin derivatives may be either through the induction of apoptosis or by inhibition of neovascularization [4,5]. The free radical hypothesis supported the fact that the antioxidants effectively inhibit the tumor, and the observed properties may be attributed to the antioxidant and antitumor principles present in the betulin contained dosage forms.…”
Section: Discussionmentioning
confidence: 99%
“…The most promising approach in therapy is the use of natural substances with cytotoxic activity concerning tumor cells but not affecting healthy ones. Such substances include lupane triterpenoids-betulin, betulinic and betulonic acids and their derivatives [1][2][3][4][5][6][7]. Recent studies have shown that the combination of triterpenoids such as oleanolic, ursolic and betulinic acids with 5-fluorouracil might be a useful tool with reduced doses of an anticancer drug-5-fluorouracil and without any side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis usually takes three or more stages with a maximum betulinic acid yield of 55% [1]. BA has a wide range of anti-tumor effects and exhibits anti-HIV activity [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%